Impact of urban green space on self-rated health: Evidence from Beijing - Zhan, Dongsheng; Zhang, Qianyun; Kwan, Mei-Po; Liu, Jian; Zhan, Bochuan; Zhang, Wenzhong (Frontiers in Public Health, 2022)
As a crucial component of urban green space (UGS), urban parks have been found to be closely associated with the health of urban residents. Drawing on a large-scale survey, ‘International First-class Harmonious and Livable Capital’, in Beijing conducted in 2018, this paper examines the impact of subjective and objective characteristics of UGS on residents’ self-rated health (SRH) by using a binary logistic regression model. The results indicate that the overall SRH status of urban residents in Beijing is relatively good, with 73.8% of the respondents reporting good SRH. The perceived quality of UGS and objectively measured accessibility to UGS are positively associated with residents’ SRH, but the subjective indicator of UGS has a greater impact on SRH than the objective indicator of UGS. In terms of influencing mechanisms, social interaction and air quality perception were the two major mediators of UGS that affected residents’ SRH. The heterogeneity analysis suggests that objective accessibility to different types of urban parks has mixed effects on residents’ SRH. Access to high-quality parks is positively associated with residents’ SRH, whereas access to common parks has a negative impact on residents’ SRH. Our findings provide important policy implications for optimising urban park design and improving the quality of urban park provision according to human needs in the Beijing Metropolitan Area.